Sodno varstvo pravic v zdravstvu - Mohorič Kenda, Anka (Javna uprava, 2023)
The article summarises the international legal bases that underpin the commitments of the Member States of the European Area of Justice to implement judicial protection of rights in healthcare. It presents an approach for the European Court for Human Right’s decision on assessing sufficient just satisfaction under Article 41 of the European Convention of Human Rights (ECHR) in inter- -state cases, which is ordered by a court against an injured party in civil litigation and is based on compensation for the interference with the mental and physical integrity of the victim in the health care sector. This article examines court decisions awarding just pecuniary compensation for non-pecuniary damage, as well as cases in which just satisfaction” is awarded. The article offers a different perspective on the meaning of just satisfaction in healthcare. It is based on a review of case-law of international courts and courts in the Republic of Slovenia. It discusses the understanding of the institute of just satisfaction when the injured party is a victim of a violation of rights under the ECHR and its Protocols and of just pecuniary compensation for non-pecuniary damage. Special attention is paid to the effect of the establishment of the institute of just satisfaction in the health care sector. It explains the significance of the recognition of just satisfaction by national courts in the context of the effective exercise of judicial protection of rights in the health sector, which should ensure not only formally and theoretically, but also in case-law, the possibility of effective implementation of the provision of Article 41 of the ECHR.
Keywords: approach to non-pecuniary damage; civilno pravo; effect of just compensation; odškodnine; pacientove pravice; pravica do sodnega varstva v zdravstvu; right to justice in healthcare; učinek pravičnega zadoščenja; victim in healthcare; žrtve v zdravstvu